Implementasi Metode Pakitani dalam Upaya Peningkatan Kualitas Hafalan Al Qur’an Mahasiswi Ma’had ‘Aly Imam Bukhari Karanganyar - Ridha, Ahmad Rasyid; Munzillah, Indiarti Muafiqoh; Ahmada, Futiha Alambarra Amaan; Zubaidah, Citra; Azkiyah, Azkiyah (TSAQOFAH, 2025)
Tahfidz or memorization of the Qur'an is a process to maintain, guard, and preserve the purity of the Qur'an which was revealed to the Messenger of Allah (peace and blessings of Allaah be upon him) by memorizing it outside the head so that there is no change and falsification and can guard against forgetfulness either in whole or in part. . The need for a structured method and a competent supervisor in memorization so that mistakes do not occur and the memorization process is easier. This study examines the Pakistani method applied in Ma'had 'Aly Imam Bukhari in the Syu'bah Lughah department in semester 4. The results obtained are that this method is quite effective to be used in carrying out the method of memorizing the Qur'an. Female students who graduated from high school or Islamic boarding schools can follow using this method. This research is a field study research that uses a qualitative descriptive approach. In data collection, this research is carried out by means of observation and direct interviews and applying the literature study method by studying and searching for data sourced from documents that are in accordance with the research topic. The data obtained is then processed and analyzed until conclusions can be drawn from all findings. All findings that have been analyzed are then described in the form of descriptive explanations to provide a broad, comprehensive, and in-depth picture.